Insect–Antioxidants Symbiotic Nexus—Pathway for Sustainable and Resilient Aquaculture: A Case Study for Evaluating Koi Carp Growth and Oxidative Stress Status - Alina Antache; Ira-Adeline Simionov; Ștefan-Mihai Petrea; Aurelia Nica; Puiu-Lucian Georgescu; Lăcrămioara Oprică; Marius-Nicușor Grigore; Mircea Oroian; Daniela Jitaru; Andreea Liteanu; Alin-Stelian Ciobîcă; Vladimir Poroch (Antioxidants)
Various innovative fish feeds were tested for the production of koi carp in a recirculating aquaculture system, considering insect meal (Acheta domestica) as the main protein source and phytogenic additives (Curcuma longa—turmeric and Beta vulgaris—beetroot) as antioxidants, in the spirit of sustainable aquaculture practice. The growth performance, metabolic rate (respirometry), hematological profile, blood biochemical indicators, and oxidative stress of koi carp were determined, using feeds according to the following experimental design: CF—commercial feed, IF—innovative feed based on cricket meal, BIF—innovative feed (IF) with beetroot, and TIF—innovative feed (IF) with turmeric. The TIF recorded the best growth rate. The lowest values of lipid peroxidation (MDA), standard metabolic rate (SMR), and routine metabolic rate (RMR) were registered for the IF and TIF variants. A reduction in MDA was noted, correlated to the decrease in the metabolic rate regarding SMR and RMR for the IF and TIF. An intensification in amylase was recorded in the TIF and BIF. Compared with the CF, it seems that the IF, TIF, and BIF had a beneficial effect on the koi carp by reducing cholesterol, HDL cholesterol, alanine aminotransferase, triglycerides, and urea and by increasing the concentration of calcium and growth hormone in the blood plasma.